Association Between Uric Acid and Renal Hemodynamics: Pathophysiological Implications for Renal Damage in Hypertensive Patients. Issue 10 (25th March 2016) - Geraci, Giulio; Mulè, Giuseppe; Mogavero, Manuela; Geraci, Calogero; Nardi, Emilio; Cottone, Santina
Abstract : The role of vascular renal changes in mediating the association between serum uric acid (SUA) and renal damage is unclear. The purposes of this study were to investigate the relationship between SUA and renal resistive index (RRI), assessed by duplex Doppler ultrasonography, and to assess whether hemodynamic renal changes may explain the association between SUA and renal damage in hypertensive patients. A total of 530 hypertensive patients with and without chronic kidney disease were enrolled and divided into SUA tertiles based on sex‐specific cutoff values. RRI and albuminuria were greater and glomerular filtration rate (GFR) was lower in the uppermost SUA tertile patients when compared with those in the lowest tertiles (all P <.001). Moreover, SUA strongly correlated with RRI ( P <.001) in all patients. However, RRI did not seem to explain the relationship between SUA and renal damage, and GFR significantly related with SUA in the overall population ( P <.001) even after adjustment for RRI.